Expanding the Active Mind. Issue 53 (3rd April 2022) - Slaby, Jan
ABSTRACT: What I call the active mind approach revolves around the claim that what is "on" a person's mind is in an important sense brought on and held on to through the agent's self-conscious rational activity. In the first part, I state the gist of this perspective in a deliberately strong way in order to create a touchstone for critical discussion. In the second part, I engage with two categories of our mental lives that seem to speak against construing the mind as active. First, I discuss affectivity, in particular emotion, and show that emotional episodes are active engagements. Second, I discuss habitual action, and in particular those manifestations of habit which are initially opaque to the agent. In my responses to both objections, the notion of a practical self-understanding will play a central role. The result will be a qualified defence and expansion of the active mind position.